Hadith #2545 - Sunan Abi Dawud - Abu Zara' al-Razi أبو زرعة الرازي; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري; Musa bin Mrwan موسى بن مروان; Yahya bin Sa'id bin Hiyan يحيى بن سعيد بن حيان (Sunan Abi Dawud)
The Prophet (ﷺ) said: The most favoured horses are the sorrel.
Grade: Hasan

Hadith #2944 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; al-Mustward bin Shadad; Jubayr bin Nufayr al-Hadrami; Musa bin Mrwan موسى بن مروان (Sunan Abi Dawud)
‘Umar reported me to collect the sadaqah (i.e. zakat). When I became free, he ordered to give me payment for it. I said: I have worked for the sake of Allah. He said: Take what you have been given, for I held an administrative post in the time of the Messenger of Allah (ﷺ), and he gave me payment for it.
Grade: Sahih

Hadith #3200 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Musa bin Mrwan موسى بن مروان; Shu'aib bin Ishaq bin 'Abdur Rahman شعيب بن إسحاق بن عبد الرحمن; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
I was present with Marwan who asked AbuHurayrah: Did you hear how the Messenger of Allah (ﷺ) used to pray over the dead? He said: Even with the words that you said. (The narrator said: They exchanged hot words between them before that.) Abu Hurairah said: O Allah, Thou art its Lord. Thou didst create it, Thou didst guide it to Islam, Thou hast taken its spirit, and Thou knowest best its inner nature and outer aspect. We have come as intercessors, so forgive him. Abu Dawud said: Shu’bah made
Grade: Hasan

Hadith #3626 - Sunan Abi Dawud - Abd al-Whab bin Njd'h عبد الوهاب بن نجدة; Auf bin Malik bin Nadlah عوف بن مالك بن نضلة - أبو الأحوص; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Khalid bin Ma'dan خالد بن معدان; Musa bin Mrwan موسى بن مروان; Syf bin Sulaiman سيف بن سليمان (Sunan Abi Dawud)
The Holy Prophet (ﷺ) said to Ibn Suriya’: I remind you by Allah Who saved you from the people of Pharaoh, made you cover the sea, gave you the shade of clouds, sent down to you manna and quails, sent down you Torah to Moses, do you find stoning (for adultery) in your Book? He said: You have reminded me by the Great. It is not possible for me to belie you. He then transmitted the rest of the tradition.
Grade: Sahih

Hadith #4710 - Sunan Abi Dawud - Abd al-Whab bin Njd'h عبد الوهاب بن نجدة; Abdullah bin Abi Labid عبد الله بن أبي لبيد; Aisha bint Abi Bakr; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Kathir bin 'Ubaid bin Nmyr كثير بن عبيد بن نمير المذحجي; Muhammad bin Harb al-Wasti محمد بن حرب بن حرمان النشائي; Muhammad bin Ziyad محمد بن زياد القرشي; Musa bin Mrwan موسى بن مروان (Sunan Abi Dawud)
Do not sit which those who believe in free will and do not address them before they address you.
Grade: Da'if

Hadith #5114 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Musa bin Mrwan موسى بن مروان; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
if a man becomes the client of any people without the permission of his patrons (i.e. those who have freed him), on him will be the curse of Allah, of angels and of all people; no obligatory or supererogatory worship will be accepted from him.
Grade: Sahih